Sensing schedule optimization to minimize interference with primary users in cognitive radio network - Suddhendu DasMahapatra; Ishita Gandhi; Kartik Nair; Shivendra Nath Sharan (Institute of Advanced Engineering and Science, 2020)
Radio Frequency (RF) spectrum, which is a limited resource, is facing the challenge of fulfilling the need of ever-growing users. To accommodate these users in an efficient manner, the idea of Cognitive Radio (CR) was proposed. It allows unlicensed users to use the licensed bands when the primary user is not using its band. To check the availability of the free spectrum, the system should be able to sense the RF environment around it, thus spectrum sensing becomes an important aspect of CR. In this work, the Genetic Algorithm (GA) is used to determine the periodic sensing schedule to maximize the number of transmission opportunities for unlicensed band users as well as to minimize interference with licensed users. This optimization scheme generates a maximum number of transmission opportunities with minimum interruption to the licensed user’s communication. The MATLAB software is used for simulation.